Corporate Governance, International Cross Listing and Home Bias - SEGAL, Dan (Institutional Knowledge at Singapore Management University, 2003)
Presents a study that examined Canadian and U.S. firms listed in the equity market from 1990 to 2000, based on book-to-market and earnings-to-price multiples. Impact of corporate governance on equity valuation; Information on regressions using exclusively Canadian-listed and Canadian cross-listed firms from 1991 to 2000; Effect of cross-listing on home bias.